Spectrum of views of the late Professor Amales Tripathi in history, literature, and philosophy (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
Amales Tripathi was a brilliant teacher at Presidency College and the University of Calcutta. He was academically associated with the Asiatic Society, Calcutta. Tripathi's study deals with Bengal during a period in which the great Presidency served as the political, financial, and commercial base of the East India Company. Tripathi touches on many aspects of the trade, shipping, and finances of the Company in Bengal. His initial research work was in economic history, and the doctoral thesis was published as Trade and Finance in Bengal Presidency, 1793- 1833. The work remains the standard work on agency houses and private trade under Company rule in Bengal. Professor Tripathi was highly influenced by F. P. Braudel’s monumental work The Mediterranean and the Mediterranean World in the Age of Philip II (translated from French into English in 1972-73). Even he was also influenced by Holden Furber’s John Company at Work, the first in-depth analysis of the English East India Company‘s Asian activities between 1783 and 1793 and by C. H. Philips’s The English East India Company 1789-1834(1940) which was based on Namerian philosophy. Professor Tripathi discarded the over simplifying approach and denunciatory tone.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(1), 2023, pp. 134-145